The social impact of AIDS in the twentieth century - Balarezo López, Gunther (2017)
AIDS was a health problem that had a strong social impact by misinformation of the people, which led to discrimination against patients and their families. In this regard, it became a literature review on some social aspects of AIDS in the late twentieth century, analyzing and summarizing the most relevant aspects of various publications. It is emphasized that the media played a crucial role in the information society, which was often fatalistic, affecting different population groups, through discrimination was provided. But the most terrible enemy was not the virus itself but prejudices, values and ignorance of society who had regarding this disease.